Patients with acute coronary syndromes express enhanced CD40 ligand/CD154 on platelets. Issue 6 (1st December 2001) - Garlichs, C D; Eskafi, S; Raaz, D; Schmidt, A; Ludwig, J; Herrmann, M; Klinghammer, L; Daniel, W G; Schmeisser, A
Abstract : OBJECTIVE: To investigate whether CD40L/CD154 on platelets and soluble CD40L/CD154 may play a role in the inflammatory process of acute coronary syndromes. DESIGN AND SETTING: Observational study in a university hospital. PATIENTS: 15 patients with acute myocardial infarction, 25 patients with unstable angina, 15 patients with stable angina, and 12 controls. MAIN OUTCOME MEASURES: CD40L/CD154 on platelets, P-selectin/CD62P on platelets, soluble CD40L/CD154 serum concentrations. RESULTS: Mean (SD) CD40L/CD154 expression on platelets was 6.2 (2.8) MFI (mean fluorescence intensity) in the infarct group, 11 (3.3) MFI in the unstable angina group (p < 0.001 v infarction), 3.6 (0.9) MFI in the stable angina group (p < 0.01 v infarction; p < 0.001 v unstable angina), and 3.2 (1.0) MFI in the controls (p < 0.01 v infarction; p < 0.001 v unstable angina; NS v stable angina). Soluble CD40L/CD154 concentration was 5.2 (1.1) ng/ml in the infarct group, 4.2 (0.7) ng/ml in the unstable angina group (p < 0.001 v infarction), 2.9 (1.0) ng/ml in stable angina group (p < 0.001 v infarction and unstable angina), and 3.0 (0.5) ng/ml in the controls (p < 0.001 v infarction and unstable angina; NS v stable angina). At a six months follow up, there was lower expression of CD40L/CD154 on platelets in patients with unstable angina (12.3 (3.6) v 3.8 (1.2) MFI, p < 0.0001) and acute myocardial infarction (6.2 (2.8) v 3.5 (0.8) MFI, p < 0.01) compared with their admission values six months earlier. Patients with unstable angina who needed redo coronary angioplasty (PTCA) or who had recurrence of angina were characterised by increased CD40L/CD154 expression on platelets compared with the remainder of the study group (recurrence of angina: 12.7 (3.2) v 9.7 (1.6) MFI, p < 0.05; re-do PTCA: 14.3 (4.2) v 10.3 (2.1) MFI, p < 0.05). CONCLUSIONS: Both CD40L/CD154 on platelets and soluble CD40L/CD154 are raised in patients with unstable angina and myocardial infarction. These findings suggest that CD40–CD40L/CD154 interactions may play a pathogenic role in triggering and propagation of acute coronary syndromes.